24.1k views
5 votes
Solve the equation 6p=2(5-2p).

First, divide both sides by 2 and simplify.
6p=2(5-2p)
2p)
6p 2(5-2p)
2
2
p=5-2p

Solve the equation 6p=2(5-2p). First, divide both sides by 2 and simplify. 6p=2(5-2p-example-1
User Mariuss
by
5.5k points

1 Answer

6 votes

Answer: 3

Explanation:

We are given that they have divided both sides of the equation by 2 and simplified the right side of the equation. We must simplify the left one.

Given:


\displaystyle (6p)/(2) =(2(5-2p))/(2)

Divide:

We know that 6 / 2 = 3, so 6p / 2 = 3p.

3p = 5 - 2p

This gives us our answer. A 3 belongs in the box given,
\boxed{3}p = 5 - 2p

User Ever Alian
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.